The Effectiveness of The Implementation of ISO 21001:2018 In the Quality Management of State Islamic Universities: A Study of Its Impact on Institutional Accreditation - Rokhmah, Siti; Amris, Amris; Yudiawan, Agus (Journal of Quality Assurance in Islamic Education (JQAIE), 2025)
This study aims to analyze the effectiveness of implementing ISO 21001:2018, the Quality Management System, in State Islamic Universities and its contribution to improving the quality and outcomes of institutional accreditation. This research used a literature study approach, reviewing books, indexed international and national scientific articles, the web (internet), and several other relevant literature sources. Data were analyzed through data reduction, data display, and conclusion/ verification. The results of the study show that the effectiveness of ISO 21001 implementation in State Islamic Universities is influenced by three main factors: transformational leadership, the internalization of a quality culture, and the integration of digital-based quality systems. All three encourage the creation of transparent, efficient, and sustainable academic governance. In addition, the implementation of ISO 21001 has been proven to strengthen the alignment between the internal quality assurance system and the BAN-PT national accreditation standards through an evidence-based approach. The integration of Islamic values, such as ihsan, amanah, and istiqamah, also enriches the implementation of the quality system by adding distinctive ethical and spiritual dimensions. This study concludes that ISO 21001:2018 is not only an administrative instrument, but also a reflective framework that forms a culture of sustainable quality in State Islamic Universities. The study’s results recommend policy synergy among the Ministry of Religion, BAN-PT, and ISO certification bodies to expand the adoption of a spirituality-based quality system and global standards in the Indonesian Islamic higher education environment.